Handover Sebagai upaya Peningkatan Keselamatan Pasien (Patient Safety) di Rumah Sakit - Triwibowo, Cecep; Yuliawati, Sulhah; Husna, Nur Amri (Jurnal Keperawatan Soedirman, 2016)
Communication on various information about the patient's progress is a fundamental component in patient safety. Transfer information in handover is essential to ensure the effectiveness and safety in patient care. The purpose of this research is to know the a relationship between handover with patient safety. The methods of this research used analytic correlative with cross sectional approach. This research used total sampling that is 62 nurses at Sidawangi Hospital West Java Province. Collecting data using closed questionnaire. Data were analyzed using chi square. The result of research showed 53.2 % nurses is implement handover included of good category and 51.6%Ã‚Â  patient safety included of good category. Statistical test showed a significant relationship between the implementation of the handover with patient safety in the hospital with a P value of 0.04. The conclusion that the handover contribute to patient safety in hospitals.